Kicz i Holokaust, czyli pedagogiczny wymiar ekspozycji muzealnych - Ziębińska-Witek, Anna (Zagłada Żydów. Studia i Materiały, 2010)
Museum exbibition is a medium consisting of multiple media but the whole is something more that the sum of its parts. Each exhibition is a kind of spectacle, a specific cultural creation, and it works according to its own rules. An exhibition is also the core of museum experience and, as such, it should be subject to multidimensional analysis. Meanwhile, the content of an exhibition and the material used in its construction are often assessed, and very little is said about it as a form of expression and the specific character of its influence on the public. In the article I analyze the exhibition in the United States Holocaust Memorial Museum in Washington in terms of the kitsch category. The term itself is hardly precise and it is multidimensional. Therefore I define it for the purposes of the and test to what extent it can be used to interpret goals and principles of assumptions behind historical exhibition dedicated to the Holocaust. The article is an exemplary interpretation of exhibition’s poetics and policy and it aims at demonstrating how pedagogical functions of museum exhibitions about the Holocaust may reduce its dimension to a lesson on intolerance.